Rate constants for the formation of CS by radiative association. Issue 4 (30th June 2018) - Forrey, R C; Babb, J F; Stancil, P C; McLaughlin, B M
ABSTRACT: Rate constants for the formation of carbon monosulfide (CS) by radiative association are calculated using accurate molecular data. The rate constants include both direct and indirect formation processes. The indirect processes (inverse rotational and electronic predissociation) are evaluated for conditions of local thermodynamic equilibrium (LTE) and also in the non-LTE limit of zero radiation temperature and atomic density. Phenomenological rate constants for CS formation in realistic astrophysical environments are expected to lie in-between these limiting cases. An analytic formula is used to fit the rate constants for convenient use in astrophysical models. The impact of the results on various astrophysical environments is briefly discussed.